N,S-Heterocyclic Carbene Containing Benzothiazol-2 and Pd (II) New Complexes Functionalized with Butyl Linked Carbazole Moiety: Synthesis, Characterization and Their Catalytic Efficiency and Electropolymerizations - Karakas, Hayriye; Guzel, Merve; Ak, Metin; Kilincarslan, Rafet; Ozdemir, Namik (Pergamon-Elsevier Science Ltd, 2022)
In contrast to the large number of polymeric N-heterocyclic carbenes (NHCs) there are relatively few examples of NHCs-containing conductive polymers. However, conducting polymers (CPs) could be excellent hosts for NHC compounds, as they can easily form polymer films electrochemically, and their optical & electrical properties can be easily tuned by electrochemically or changing bonding groups in their structure. In this work, the N,S-heterocyclic carbene (NHC) ligand precursor, N-(4-butylcarbazole)benzothiazolium bromide (1) was prepared by solvent-free alkylation of benzothiazole by 9-(4-bromobutyl)carbazole with high efficiency. The air- and moisture-stable new piano-stool Ru(II)-N,S-NHC (2) and PEPPSI type Pd(II)-N,S-NHC (3) complexes, were synthesized and characterized by H-1- and C-13 NMR, FT-IR, UV-vis and ESI-MS spectroscopic methods and elemental analysis. Further confirmations of structural details for benzothiazolium salt (1) and its Ru(II)-N,S-NHC complex (2) were determined by X-ray single-crystal diffraction. The catalytic performance of the complexes (2 and 3) in transfer hydrogenation (TH) of acetophenone and Suzuki-Miyaura cross-coupling reactions of aryl bromides were also investigated, respectively. All compounds (1-3) were electrochemically polymerized and conducting polymer films with pendant carbene complex moieties were obtained. The electrical and optical properties of the resulting polymers were characterized via spectroelectrochemical studies.
Özdemir, Namık/0000-0003-3371-9874; Güzel, Merve/0000-0002-0603-3933; Tuncer, Hayriye/0000-0002-4261-5965; Kilinçarslan, Rafet/0000-0001-6982-9536; Ak, Metin/0000-0002-0000-4613;
Keywords: N,S-Heterocyclic Carbene; Benzothiazole-2-Ylidene; Benzothiazolium Salt; Solvent-Free Alkylation; Electropolymerization; Carbazole; Catalyst; Carbene Precursor